Membangun Mental Kewirausahaan melalui Edupreneurship bagi Pendidik PAUD - Sumiyati Sumiyati (Universitas Al-Hikmah Indonesia, 2017)
Edupreneurship is an important branch of science to be taught at every level of education. Everyone has the right to be entrepreneur, including the educators on Early Childhood Education services (PAUD). PAUD Educators have a strategic opportunity as entrepreneurs by looking at the needs of learning media for children, in the form of Educational Game Tools (APE) needed to support learning, as well as the readiness of innovative teaching materials in order to create quality learning. With edupreneurship, PAUD educators will have an entrepreneurial mentality and become an independent person who is able to innovate and be creative to develop themselves into competent PAUD educators. PAUD educators will be able to become entrepreneurs by developing media products and teaching materials, as well as being an idolized teacher because it can create a learning atmosphere in the classroom with great fun with the products of these teaching materials. Edupreneurship can also be introduced to children through aspects of child development, such as aspects of moral values development, aspects of language development, emotional social development aspects of independence, aspects of physical motor development, aspects of cognitive development and aspects of art development.